Label-free Impedimetric Immunosensors for Liver Cancer Stem Cells. (2017) - Eissa, Shimaa; Chinnappan, Raja; Zourob, Mohammed
Abstract: Liver cancer is considered the fifth most common cancers in the world and the second cause of cancer death in men. Cancer stem cells (CSCs) are a small subset of cancer cells that have been recently proposed to be responsible for tumor relapse, metastasis, and chemoresistance. Here, we report the development of label-free electrochemical immunosensors for CSC detection using four cell surface biomarkers (CD44, CD90, CD133/2 and OV-6). The immunosensors were fabricated by covalent immobilization of the four specific antibodies for the biomarkers on gold electrodes via cysteamine/phenylene isothiocyanate linker. Electrochemical impedance spectroscopy was utilised to monitor the binding of the CSCs to the immunosensors. The binding of the cells to the electrode surface blocks the electron transfer between [Fe(CN)6 ] 3-/4− redox probe and the gold electrode causing an increase in the charge transfer resistance (Rct ). This change in the Rct represents the basis of the CSC biosensing. The developed immunosensors showed high sensitivity and selectivity for CSC detection with a wide dynamic range from 1 × 10 1 to 1× 10 6 cells/mL. This work opens up new, accurate, simple and low cost avenue for the detection of liver CSC that might help in the early diagnosis and treatment of liver cancer.